Risk of Higher Blood Pressure in 3 to 6 Years Old Singleton Born From OHSS Patients Undergone With Fresh IVF/ICSI - Zhu, Yimin; Fu, Yanling; Tang, Minyue; Yan, Huanmiao; Zhang, Fanghong; Hu, Xiaoling; Feng, Guofang; Sun, Yu; Xing, Lanfeng (Frontiers in Endocrinology, 2022)
Background A large registry-based study found the increasing disorders of cardiovascular and metabolism in IVF children but underlying mechanism is still unknown. Few studies have investigated any association between OHSS and cardiovascular or metabolic function in subsequent children. Objective To evaluate the effect of ovarian hyperstimulation syndrome (OHSS) on blood pressure of singletons after in vitro fertilization (IVF) with or without intracytoplasmic sperm injection (ICSI). Study Design The singlet-center corhort study included 1780 singletons born with IVF/ICSI and 83 spontaneously conceived children from 2003 to 2014. Follow-up has lasted more than 10 years, and is still ongoing. This study analyzed data from follow-up surveys at 3 to 6 years of age. Participants, Setting and Methods We recruited 83 children (Group E) spontaneously conceived (SC) as control group and 1780 children born with IVF/ICSI including 126 children born to OHSS-fresh embryo transfer (ET) women (Group A), 1069 children born to non OHSS-ET women (Group B), 98 children conceived by women who developed into moderate or severe OHSS after oocyte retrieval and selected the frozen-thawed embryo transfer (FET) (Group C), 487 children conceived with non OHSS-FET (Group D). We evaluated cardiometabolic function, assessed BP in mmHg, heart rate, anthropometrics, and metabolic index including glucose, serum lipid (triglyceride, total cholesterol, low density lipoprotein, high density lipoprotein), thyroid function, of those children. The BP and heart rate were measured twice on the same day. We applied several multiple regression analyses to investigate the effect of OHSS in the early pregnancy. Main Findings By the single factor analysis, the SBP and DBP in the SC group (SBP: 99.84 ± 8.9; DBP: 55.27 ± 8.8) were significantly lower than OHSS-ET group’s, while the blood pressure was similar between the SC group and other three ART groups. Children had higher BP in the OHSS-ET group (SBP: 101.93 ± 8.17; DBP: 58.75 ± 8.48) than in the non OHSS-ET (SBP: 99.49 ± 8.91; DBP: 56.55 ± 8.02) or OHSS-FET group (SBP: 99.38 ± 8.17; DBP: 55.72 ± 7.94). After using multiple regression analysis to adjust current, early life, parental and ART characteristics, the differences in the SBP and DBP (B (95% confidence interval)) between OHSS-ET and non OHSS-ET remained significant (SBP: 3.193 (0.549 to 2.301); DBP: 3.440 (0.611 to 2.333)). And the BP showed no significant difference complementarily when compared non OHSS-FET group with non OHSS-ET group. In addition, the anthropometrics, fast glucose, serum lipid, and thyroid index did not differ among the ART groups. Principal Conclusions OHSS might play an independent key role on offspring’s BP even cardiovascular function. Electing frozen-thawed embryo transfer for high risk of OHSS population may reduce the risk of the high BP trend. Wider Implications of the Findings It is a large sample study to investigate the effect of OHSS on offspring’s health. These findings provide a clinic evidence of the impact of early environment (embryo even oocyte stage) on the offspring’s cardiovascular health. Our study emphasis the importance of the accuracy of IVF clinic strategy and preventing the OHSS after fresh embryo transfer.